Psychomotor evaluation model for 21st century skills in the Industrial Revolution 4.0 Era - Diah Puji Nali Brata; Edy Setiyo Utomo; Ahmad Farhan (Kasetsart Journal of Social Sciences, 2026)
The objective of this research is to examine the application of psychomotor evaluation instruments and techniques in facilitating the development of 21st century skills specifically critical thinking, communication, collaboration, and creativity among educators and learners in Indonesia at the secondary school level. The sample comprised 35 teachers and 88 students from the Jombang, Mojokerto, and Gresik regions. A questionnaire employing a four-point Likert scale was disseminated via Google Forms and WhatsApp to collect data, with the reliability and validity of the instruments established through expert judgment and pilot testing. Data analysis was conducted using the Partial Least Squares (PLS) Program version 3.0. The principal findings indicate that certain psychomotor evaluation techniques, such as performance appraisal and project evaluation, significantly influence students’ acquisition of these skills (p < .05). The innovation of the proposed psychomotor evaluation model lies in the combination of continuous tracking and a variety of assessment techniques in order to measure students’ skills more effectively. This study provides a foundation that this model can be adapted by educational stakeholders in order to improve assessment for effective skills training in students. It should also be noted that the application of the model could vary in effectiveness depending on the educational context, in particular, hands-on learning environments and collaborative educational contexts. Future research should explore interdisciplinary and cross-disciplinary applications of the model to increase its relevance and effectiveness in improving student success in the 21st century educational landscape.